1998
DOI: 10.1002/(sici)1097-0282(1998)48:2<113::aid-bip3>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

On the role of magnesium ions in RNA stability

Abstract: Divalent cations, like magnesium, are crucial for the structural integrity and biological activity of RNA. In this article, we present a picture of how magnesium stabilizes a particular folded form of RNA. The overall stabilization of RNA by Mg2+ is given by the free energy of transferring RNA from a reference univalent salt solution to a mixed salt solution. This term has favorable energetic contributions from two distinct modes of binding: diffuse binding and site binding. In diffuse binding, fully hydrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
285
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(299 citation statements)
references
References 137 publications
13
285
0
1
Order By: Relevance
“…They can either specifically coordinate with nucleic acids or through diffuse binding. [38] Overall a similar pattern was observed as shown in Figure 4A, D; Hg II can still be detected under all of the tested conditions. As shown in Figure 4B, E, the sensitivity became higher with an increasing concentration of these metal ions.…”
Section: Resultssupporting
confidence: 83%
“…They can either specifically coordinate with nucleic acids or through diffuse binding. [38] Overall a similar pattern was observed as shown in Figure 4A, D; Hg II can still be detected under all of the tested conditions. As shown in Figure 4B, E, the sensitivity became higher with an increasing concentration of these metal ions.…”
Section: Resultssupporting
confidence: 83%
“…From the spectra recorded under these solution conditions, we can conclude that Mg 2ϩ ions are replaced partially by Li ϩ and that as a result of this cation exchange only a subset of proteins remains firmly attached to the RNA scaffold in the gas phase. It is well established that Mg 2ϩ is crucial for the structural integrity of RNA interacting either by diffuse binding in which fully hydrated Mg 2ϩ binds to RNA via nonspecific long range electrostatic interactions or by site-specific interactions with anionic ligands facilitated by the RNA fold (29). The binding of Mg 2ϩ to the acidic stalk proteins observed in the present study is presumably nonspecific, because multiple adducts are observed, and demonstrates the presence of the diffuse Mg 2ϩ cloud surrounding rRNA.…”
Section: Resultsmentioning
confidence: 49%
“…Both divalent and monovalent cations bind to nucleic acid molecules and affect their physical properties (1). Magnesium cations stabilize nucleic acid duplexes and facilitate their folding into secondary and tertiary structures (2), which are biologically active. Mg 2+ ions are also necessary cofactors of many enzymatic reactions involving nucleic acids (3).…”
mentioning
confidence: 99%